Chronic infections and coronary heart disease: is there a link? - Danesh, J; Collins, R; Peto, R (1997)
A large number of studies have reported on associations of human coronary heart disease (CHD) and certain persistent bacterial and viral infections. We review the epidemiological and clinical evidence on CHD and Helicobacter pylori, Chlamydia pneumoniae, and cytomegalovirus (CMV), as well as possible mechanisms. The association between CHD and H pylori may be accounted for by residual confounding from risk factors. Although the association between C pneumoniae and CHD is stronger, the sequence of infection and disease is uncertain. As regards CMV, a limited number of patients with classic atherosclerotic coronary artery disease have been studied. Further studies are needed to resolve these uncertainties.